Are the Nation's Leading Political Science Programs Practicing the Egalitarian Values Espoused in “American Democracy in an Age of Rising Inequality”, And if Not, How Can They? - Oldfield, Kenneth (PS: Political Science & Politics, 2008)
A study was conducted to determine whether the leading political science programs in the U.S. are employing socioeconomic-based affirmative action to ensure they are enrolling a diverse student body, as advocated by the 2004 report American Democracy in an Age of Rising Inequality (ADARI) compiled by the American Political Science Association's Task Force on Inequality and American Democracy. Data were obtained through a questionnaire sent to 26 political science graduate programs in the U.S. Findings indicated that, overall, the country's leading political science programs are doing little to counteract the antidemocratic trends highlighted in ADARI. Findings revealed that the overwhelming majority of respondents make little or no effort to enroll more students from working class backgrounds. Findings are discussed in detail.